Pengaruh Literasi Keuangan, Penggunaan Electronic Wallet dan Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa (Studi Kasus Mahasiswa S1 Akuntansi Fakultas Ekonomi dan Bisnis di Universitas Muhammadiyah Metro) - Hardy, Arum Mutiara; Hendri, Nedi; Darmayanti, Elmira Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze Financial Literacy (1), Use of Electronic Wallet (2), and Self-Control (3) on Consumptive Behavior in Students of the Bachelor of Accounting Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro. The population in this study were 268 respondents. The sampling technique in this research used several respondent criteria to obtain a sample of 160 respondents. The data in this study used SPSS version 22 with multiple linear regression analysis testing. The results of this study indicate that financial literacy, use of electronic wallets, and self-control have a partial or simultaneous effect on consumptive behavior in Students of the Bachelor of Accounting Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro.